Association between ATG16L1 rs2241880(T300A) and rs4663421 and ANCA‑associated vasculitis in the Guangxi population of China: Propensity score matching analysis - Tang, Wenlv; Zhang, Yurong; Lu, Shurong; Xue, Chao (Biomedical reports, 2025)
Antineutrophil cytoplasmic antibody-associated vasculitis (AAV) is a rare autoimmune disease with an unclear pathogenesis. The present study investigated the associations between autophagy-related protein 16-like 1 (ATG16L1) rs2241880(T300A) and rs4663421 and AAV. A total of 177 patients with AAV and 216 healthy controls were included. Propensity score matching was used to match the two groups of subjects in terms of sex, age and ethnicity. Analyses of the relationships between these genetic polymorphisms and AAV susceptibility, including comparisons of allele and genotype frequency distribution, linkage disequilibrium analysis and analysis of single nucleotide polymorphism (SNP) interactions between two loci were performed. The association between the loci and laboratory test results and renal pathology were also analysed. A total of 154 pairs of patients with AAV and healthy controls was successfully matched. Neither polymorphism was associated with AAV susceptibility. However, SNP interaction in the model constructed with the two loci was statistically significant (P=0.018), and the combination of the AA genotype of rs2241880(T300A) and GG genotype of rs4663421 was associated the highest disease risk. The differences in the Birmingham Vasculitis Activity Score (BVAS), C-reactive protein (CRP) levels and 24-h urine protein level between patients with the rs2241880(T300A) AA + AG genotypes and the GG genotype were statistically significant (P<0.05). Furthermore, significant differences in the severity of glomerulosclerosis and global sclerosis were detected between individuals with the AA + AG genotype and those with the GG genotype at the rs2241880(T300A) locus (P<0.05). Similarly, there were statistically significant differences in degree of segmental sclerosis between individuals with CC + CG genotypes and those with GG genotypes at the rs2243421 locus (P<0.05). In summary, the single gene polymorphisms of these loci were not associated with genetic susceptibility to AAV. However, SNP interactions may serve a role in the risk of AAV. The rs2241880(T300A) polymorphism may be associated with BVAS, CRP levels and 24-h urine protein level in AAV. These SNPs may be associated with glomerulosclerosis and segmental sclerosis.